The effectiveness of emotion-focused therapy on emotion regulation and coping strategies of women with somatic symptom - Moloud Sivandian; Hajar Falahzade (Journal of Education and Health Promotion)
BACKGROUND: Somatic symptoms and related disorders are prevalent phenomena in the healthcare system. As the clinical observations have shown the relation of these symptoms with emotions and cognitive distortions, the present study aimed to investigate the effectiveness of emotion-focused therapy (EFT) on emotion regulation and coping strategies in women with somatic symptoms. MATERIALS AND METHODS: In this semi-experimental, two-group pretest-posttest phases study the sample consisted of 30 women with somatic symptoms aged between 20 and 60 years in the spring of 2023, who were selected through purposive sampling and randomly assigned to the experimental and control groups. To assess the research variables, the Patient Health Questionnaire (PHQ), Structured Clinical Interview for DSM-5 (SCID-I), Garnefski and Kraaij’s Cognitive Emotion Regulation Questionnaire, and Lazarus and Folkman’s Coping Strategies Questionnaire were used in both pretest and posttest phases. The EFT group received treatment for 12 sessions, while the control group remained on a waiting list. The data were analyzed using SPSS 23 software and covariance analysis. RESULTS: The results indicated that EFT improved emotion regulation and coping strategies in women with somatic symptoms in the posttest (P > 0.05). CONCLUSION: Based on the findings of this study, it appears that EFT can be used as a psychological treatment to improve emotion regulation and coping strategies in women with somatic symptoms.